Fatal acute disseminated encephalomyelitis following treated snake bite in India. Issue 4 (23rd March 2005) - Malhotra, P; Sharma, N; Awasthi, A; Vasishta, R K
Abstract : Snake bite is an important cause of mortality and morbidity in India, with an estimated 35 000 to 50 000 fatal bites occurring annually. The neurological consequences of snake bite are predominantly the result of inhibition of neuromuscular transmission. We describe the first documented case of autopsy proven acute disseminated encephalomyelitis following treated snake bite in a young female.